120 Awardee Talk: Amino acid and energy requirements of high producing sows. (5th December 2019) - Goodband, Robert; Menegat, Mariana; Gourley, Kiah; Thomas, Lori; Tokach, Mike; Dritz, Steve; Woodworth, Jason; DeRouchey, Joel
Abstract: Improvements in genetic selection, nutrition, health, and management has led to continuous improvement in sow productivity over the past 10 to 20 years. Today's sows are more prolific with greater number of pigs gestated, nursed, and weaned per litter than in the past. Modern genotype females are also faster growing and leaner than predecessors. These changes in reproductive performance and body composition alter nutrient requirements during gestation and lactation. Gestation nutrient requirements appear to be met with approximately 11 to 12 g/d of standardized ileal digestible (SID) lysine and 5, 000 to 6, 000 Kcal/d NE. Providing greater lysine intake increases protein deposition and sow weight gain and may reduce stillbirth rate; however, the magnitude of economic benefit provides marginal economic response. Increasing energy and amino acid intake the last 3 to 4 days pre-farrowing appears to be a better alternative to shorten farrowing duration, increase the number of pigs born alive, and their weaning weights, than providing extra feed from d 90 of gestation through farrowing. During lactation, the goal is still to increase feed intake to minimize sow weight loss. Lysine requirement estimates in lactation seem to vary from study to study possibly reflecting the degree of sow muscle and fat catabolism. A summary of several lactation studies predicts a daily lactation requirement of 27 g SID Lys from the diet with an additional 13 g mobilized from body tissue for each 1 kg of litter growth. From a feed management standpoint, the availability of equipment to provide ad libitum consumption has been a major benefit in lactation. In conclusion, the literature suggests there are many successful ways to feed sows in gestation, peri-partum, and lactation, indicating that today's sows are extremely resilient to nutritional challenges.